Synergic interaction between ritodrine and magnesium sulfate on the occurrence of critical neonatal hyperkalemia: A Japanese nationwide retrospective cohort study - Yada, Yukari (Sci Rep, 2020)
Our aim was to evaluate the association between ritodrine and magnesium sulfate (MgSO(4)) and the occurrence of neonatal hyperkalemia or hypoglycemia among late preterm infants in a retrospective cohort study. We used a nationwide obstetrical database from 2014. A total of 4,622 live preterm infants born at 32–36 gestational weeks participated. Fourteen risk factors based on both clinical relevance and univariate analysis were adjusted in multivariable logistic regression analyses. Neonatal hyperkalemia and hypoglycemia occurred in 7.6% (284/3,732) and 32.4% (1,458/4,501), respectively. Occurrence of hyperkalemia was associated with concomitant usage of ritodrine and MgSO(4) compared with no usage (adjusted odds ratio [aOR] 1.53, 95% confidence interval [CI] 1.09–2.15). Occurrence of hypoglycemia was associated with ritodrine alone (aOR 2.58 [CI 2.21–3.01]) and with concomitant usage of ritodrine and MgSO(4) (aOR 2.59 [CI 2.13–3.15]), compared with no usage, and was associated with long-term usage (≥ 48 hours) of ritodrine and cessation directly before delivery. In conclusion, in late preterm infants, usage of ritodrine together with MgSO(4) was associated with occurrence of critical neonatal hyperkalemia, and long-term usage of ritodrine and cessation directly before delivery were associated with neonatal hypoglycemia.